Applicability and relevance of six indoor air quality indexes. (15th November 2016) - Wei, Wenjuan; Ramalho, Olivier; Derbez, Mickaël; Ribéron, Jacques; Kirchner, Séverine; Mandin, Corinne
Abstract: The evaluation of indoor air quality (IAQ) in buildings is complex because IAQ involves a broad spectrum of substances and agents that vary over time and space. To address this complexity, IAQ indexes are used to describe, classify and improve IAQ by providing easy-to-understand and comprehensive rankings of IAQ levels in buildings. Although many IAQ indexes have been proposed all over the world, their relevancy regarding the evaluation of IAQ levels has not been fully studied in a large number of dwellings. In this study, six measurement-based IAQ indexes proposed for use in the USA, France, Taiwan, and Hong Kong were evaluated. The calculation of IAQ levels was based on nine indoor parameters measured in 567 French dwellings, i.e., indoor air temperature, relative humidity, and concentrations of formaldehyde, total volatile organic compounds, radon, carbon monoxide, carbon dioxide, PM2.5, and PM10 . A factorial analysis using the multiple correspondence analysis and the hierarchical cluster analysis methods was performed to determine whether the calculated IAQ levels of different indexes in the studied dwellings were repeatable across all indexes. The results showed that three of the indexes tended to provide only positive IAQ ratings, while the other three indexes were more discriminating. Three classes of IAQ levels in dwellings, along with indoor parameters associated with each class, were identified. All of the indoor parameters were associated with the classification of IAQ levels, while the formaldehyde concentration and relative humidity were the key parameters to identify the dwellings with the best IAQ. Highlights: The applicability and relevance of six measurement-based IAQ indexes were evaluated. The IAQ calculation was based on measured parameters in 567 French dwellings. The indexes suggest that 34% of the assessed dwellings had an unfavorable IAQ. The indexes are not fully consistent in determining dwellings with a good IAQ.